A qualitative study of fourteen African countries' nursing workforce and labour market. (10th May 2021) - Bryant, A.; Reynolds, N.R.; Hart, L.; Johnson, P.G.; Kalula, A.; Gokul, B.; Davidson, P.M.
Abstract : Aim: The aim of this study was to describe factors affecting nursing education and labour markets in countries in East, Central, and Southern Africa, and critical areas for investment. Background: An understanding about the relationship between the supply of nurses (determined by types of educational programmes, and the quantity and quality of nurse graduates), and workforce demand is critical to health policy development. Methods: Six focus groups and 14 key informant interviews with nursing leaders and experts were conducted. Participants included government chief nursing officers, registrars of regulatory bodies, association leaders and heads of nursing education. The data were transcribed, coded and analysed using inductive techniques. Findings: Participants discussed challenges and strengths of nursing education, school and regulatory infrastructure, financing mechanisms for the nursing workforce, the state of nursing jobs and scope of nursing practice. Conclusion: Strengthened regulations and leadership are needed to improve investment in nursing, the quality of nursing education, and working conditions and to promote the achievement of better health outcomes. Implications for Nursing Policy: Clarifying scope of practice for nurses in the health sector and creating competency‐based requirements is important. Governments should establish positions that align with updated competencies and provide fair and safe working conditions. The current and ongoing investment case for nursing requires improved data systems and a commitment to use labour market data for decision‐making.